2011
DOI: 10.1016/j.jcis.2011.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HIV-1 fusion peptide inhibition by synthetic peptides from E1 protein of GB virus C

Abstract: The aim of this study was to identify proteins that could inhibit the activity of the peptide sequence representing the N-terminal of the surface protein gp41 of HIV, corresponding to the fusion peptide of the virus (HIV-1 FP). To do this we synthesized and studied 58 peptides corresponding to the envelope protein E1 of the hepatitis G virus (GBV-C). Five of the E1 synthetic peptides: NCCAPEDIGFCLEGGCLV (P7), APEDIGFCLEGGCLVALG (P8), FCLEGGCLVALGCTICTD (P10), QAGLAVRPGKSAAQLVGE (P18) and AQLVGELGSLYGPLSVSA (P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Water was double distilled and deionized (MilliQ system, Millipore; 18.2 MW cm Methods: Peptide Synthesis: P7, P8, P10, P18, and P22 were obtained by solid-phase methodologies and purified by preparative HPLC, as previously described. [19] The fusion peptide of the HIV-1 glycoprotein gp41, HIV-1 FP/AVGIGALFLGFLGAAGSTMGAAS, was also synthesized manually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water was double distilled and deionized (MilliQ system, Millipore; 18.2 MW cm Methods: Peptide Synthesis: P7, P8, P10, P18, and P22 were obtained by solid-phase methodologies and purified by preparative HPLC, as previously described. [19] The fusion peptide of the HIV-1 glycoprotein gp41, HIV-1 FP/AVGIGALFLGFLGAAGSTMGAAS, was also synthesized manually.…”
Section: Discussionmentioning
confidence: 99%
“…Results have shown that five peptide sequences corresponding to the envelope protein E1 of GBV-C [NCCAPEDIGFCLEGGCLV (P7), APEDIGFCLEGGCLVALG (P8), FCLEGGCLVALGCTICTD (P10), QAGLAVRPGKSAAQLVGE (P18), and AQLVGELGSLYGPLSVSA (P22)] were capable of interfering with the HIV-1 FP-vesicle interaction. [9] Consequently, Five peptide sequences corresponding to the E1 protein of GBV-C [NCCAPEDIGFCLEGGCLV (P7), APEDIGFCLEGGCLVALG (P8), FCLEGGCLVALGCTICTD (P10), QAGLAVRPGKSAAQLVGE (P18), and AQLVGELGSLYGPLSVSA (P22)] were synthesized because they were capable of interfering with the HIV-1 fusion peptide (HIV-1 FP)-vesicle interaction. In this work the interaction of these peptides with the HIV-1 FP, as well as with membrane models, was analyzed to corroborate their inhibition ability and to understand if the interaction with the fusion peptide takes place in solution or at the membrane level.…”
Section: Introductionmentioning
confidence: 99%
“…The GBV-C E2 protein directly inhibits HIV pseudovirus entry, and peptides derived from the E2 protein interfere with HIV cellular binding and fusion, independent of the viral effect on CD4 cell homeostasis [33, 34]. Synthetic peptides derived from GBV-C E1 protein also inhibit HIV entry, and appear to interact with HIV fusion peptides [37]. By contrast, NS5A protein expression downregulates CXCR4 surface expression and induces the release of the CXCR4 ligand (SDF-1) in CD4 + T cells [35, 36].…”
Section: Gbv-c Interactions With Hivmentioning
confidence: 99%
“…Our group has been performing in vitro physical and chemical studies with GBV-C peptide sequences that have proven to be effective as potential inhibitors of HIV-1 FP, yielding results on the interaction of the virus with several sequences of interest [8][9][10][11][12]. HIV-1 FP and GBV-C peptides have amphiphilic properties that allow them to undergo self-assembly in aqueous solution to form various nanoscale architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Surface behaviour at the air-water interface [15][16][17], and in peptide-lipid binding assays [11,18,19], leakage assays, fluorescence anisotropy or fluorescence resonance energy transfer studies [20,21] have each been applied to find a correlate between the capacity to inhibit HIV-1 FP in vitro and in vivo during cell-cell fusion inhibition studies [10,15]. In addition, topographical characterisation of model membranes showing the changes caused by HIV-1 FP or GBV-C peptides in various mixtures have been obtained by fluorescence microscopy (FM) and atomic force microscopy (AFM) [22,23].…”
Section: Introductionmentioning
confidence: 99%